Gait bradykinesia: difficulty in switching posture/gait measured by the anatomical y-axis vector of the sole in Parkinson’s disease - Warabi, Tateo; Furuyama, Hiroyasu; Kato, Masamichi (Experimental brain research, 2020)
This study in Parkinson’s disease examined how spatiotemporal parameters in gait bradykinesia link to difficulty in terminating posture and initiating gait locomotion. 41 idiopathic Parkinson’s disease patients and 15 age-matched healthy subjects participated in this study. After the patients fixated on a visual-fixation-target, gait was triggered by visual or vocal cue-stimulus. The LED instructed subjects to quickly achieve their own comfortable walking speed on a level floor. The posterior-anterior force of the y -axis vectors of sole relating to soleus and tibialis-anterior EMGs were examined. Step-gain was defined as the duration of the swing-phase relative that of the contralateral stance-phase. Dynamic-ratio was defined as the duration the fore-foot phase relative to that of the ipsilateral stance-phase as forward-oriented movement in each step. The pause in tonic soleus EMG was defined as the off-latency of posture (termination) and the onset of a tibialis-anterior EMG-burst as the on-latency of gait. In Parkinson’s disease, soleus off-latencies were prolonged, whereas tibialis-anterior on-latencies were less prolonged. Unsynchronized off/on-latency differences correlated with spatiotemporal parameters of dynamic-ratios, step-gains, gait-initiation, and gait speed in gait bradykinesia. Delayed EMG off-latencies correlated with prolonged motor-latencies in gait bradykinesia as delayed initial backward body-shift. A delayed and deficient initial backward body-shift of y -axis vector was linked to each difficulty in terminating posture and initiating gait, changing to random gait akinesia. Gait bradykinesia in Parkinson’s disease stemmed from unsynchronized off/on-latency EMG activities, linking to each difficulty in terminating posture and initiating gait synergic movement through an initial backward body-shift.